Religion and society in Qajar Iran - Gleave, R. (Robert) (RoutledgeCurzon/BIPS Persian studies series ;, 2005)
E.G. Browne relates this story in his A Year amongst the Persians in orderto demonstrate the gross ignorance which sometimes characterises [amulls] decisions. The episode was related to Browne by one of his Bbassociates in Kerman, and the question was designed to expose this ignoranceof the clergy. As it is related here, however, the jibe is unwarranted. A hole half a yard in each direction is not half a yard square (it is half ayard cubed). The mull, in the absence of a specification of depth, assumesthat the hole is dug to the same depth as the original request. This assumptionis.